Government debt: an empirical analysis with structural break for the economy of Malaysia - Shairil Izwan Taasim; Adrian Daud; Saizal Pinjaman; Mohamad Ibrani Shahrimin Adam Assim; Yasmin Yaccob (Human Resource Management Academic Research Society (HRMARS), 2021)
Malaysia recorded a fiscal policy with a deficit budget since the economic crisis in 1997. During the tough economic crisis to maintain economic growth, the government committed to stimulus fiscal budget controlling. According to the Keynesian theory, a fiscal policy may induce economic growth at moderate levels of public debt. Although debt and economic growth are not recent issues faced by the Malaysia government, the impact government debt on economic growth has been debated, especially in terms of imbalances development. This work aims to investigate the relationship between economic growth and government debt in Malaysia, with the application of structural break analysis. We utilized econometric techniques such as unit root tests and Granger. Regarding the unit root test, we used structural break combinations with pure and partial structural change models. The analysis is based on data across the period of 1970 to 2018. We find more evidence against the unit root test with structural breaks in Malaysia, with causality between debt and economic growth.